Ultrathin Iron‐Cobalt Oxide Nanosheets with Abundant Oxygen Vacancies for the Oxygen Evolution Reaction. Issue 17 (27th February 2017) - Zhuang, Linzhou; Ge, Lei; Yang, Yisu; Li, Mengran; Jia, Yi; Yao, Xiangdong; Zhu, Zhonghua
Abstract : Electrochemical water splitting is a promising method for storing light/electrical energy in the form of H2 fuel; however, it is limited by the sluggish anodic oxygen evolution reaction (OER). To improve the accessibility of H2 production, it is necessary to develop an efficient OER catalyst with large surface area, abundant active sites, and good stability, through a low‐cost fabrication route. Herein, a facile solution reduction method using NaBH4 as a reductant is developed to prepare iron‐cobalt oxide nanosheets (Fe x Co y ‐ONSs) with a large specific surface area (up to 261.1 m 2 g −1 ), ultrathin thickness (1.2 nm), and, importantly, abundant oxygen vacancies. The mass activity of Fe1 Co1 ‐ONS measured at an overpotential of 350 mV reaches up to 54.9 A g −1, while its Tafel slope is 36.8 mV dec −1 ; both of which are superior to those of commercial RuO2, crystalline Fe1 Co1 ‐ONP, and most reported OER catalysts. The excellent OER catalytic activity of Fe1 Co1 ‐ONS can be attributed to its specific structure, e.g., ultrathin nanosheets that could facilitate mass diffusion/transport of OH − ions and provide more active sites for OER catalysis, and oxygen vacancies that could improve electronic conductivity and facilitate adsorption of H2 O onto nearby Co 3+ sites. Abstract : Ultrathin iron‐cobalt oxide nanosheets (Fe x Co y ‐ONSs) rich in oxygen vacancies are prepared through NaBH4 fast reduction. Nanosheets with an equal Fe/Co ratio exhibit high oxygen evolution reaction (OER) activity. Experimental results prove that the abundant oxygen vacancies and large surface area of Fe1 Co1 ‐ONS can provide more OER active sites and facilitate mass/electron transfer, while Fe 3+ incorporation can increase the reactivity of active sites.